CERTIFICATION OF TESTING EQUIPMENT OF THE COMPONENTS AND UNITS OF AVIATION EQUIPMENT - A. A. Вogoyavlenskiy (Научный вестник МГТУ ГА, 2017)
The article sets analysis of the state organization and carrying out works on certification of testing equipment and software at tests of the components and units of aviation equipment in the organizations on repair of air transport performed by the Parent organization of the metrological service civil aviation – FSUE State scientific and research institute of civil aviation.